Pemberdayaan Ekonomi Masyarakat Berbasis Budidaya Ikan Nila Di Desa Sarang Burung Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Hansen Rusliani; Muhamad Subhan; Muhammad Arif Zidni (Jurnal Publikasi Manajemen Informatika, 2023)
The purpose of this study was to find out how the process of community economic empowerment based on tilapia cultivation in Sarang Burung Village, Jambi Outer City District, Muaro Jambi Regency, the type of research used was qualitative, while the data collection techniques used in the study were interviews and documentation. This empowerment experienced several obstacles, including the need for large capital to make cages, besides that the farmers were also faced with the problem of limited capital so that they found it difficult to buy tilapia seeds and feed. Unstable weather conditions are also often encountered by tilapia cultivation actors such as heavy rainfall, flooding which results in many dead fish and leakage of nets. Based on the results of research on community economic empowerment based on tilapia cultivation in the Bird's Nest Village, it has helped a lot in changing the economy of the village community, both cage owners and daily workers, the village government also supports all tilapia cultivation activities carried out by the community, the government also holds counseling by collaborating with the fisheries office of Muaro Jambi Regency so that tilapia farmers know more and explore the ins and outs of cultivating tilapia.